Remote ischemic conditioning provides humoural cross-species cardioprotection through glycine receptor activation. Issue 1 (9th January 2017) - José Alburquerque-Béjar, Juan; Barba, Ignasi; Valls-Lacalle, Laura; Ruiz-Meana, Marisol; Pecoraro, Michela; Rodríguez-Sinovas, Antonio; García-Dorado, David
Abstract : Aims: Remote ischaemic conditioning (RIC) releases a humoural factor able to exert cross-species cardioprotection when plasma dialysate is applied to isolated hearts. However, the exact chemical nature of this factor is currently unknown. Methods and results: RIC (4 × 5min femoral occlusion/5min reperfusion) was applied to 10 male pigs, and blood was taken before and after the manoeuvre. Discriminant analysis of 1 H-NMR spectra ( n  = 10–12) obtained from plasma dialysates (12–14 kDa cut-off) allowed to demonstrate a different metabolic profile between control and postRIC samples, with lactate (2.671 ± 0.294 vs. 3.666 ± 0.291 μmol/mL, P  = 0.020), succinate (0.062 ± 0.005 vs. 0.082 ± 0.008 μmol/mL, P  = 0.035) and glycine (0.055 ± 0.009 vs. 0.471 ± 0.151 μmol/mL, P  = 0.015) being the main responsible for such differences. Plasma dialysates were then given to isolated mice hearts submitted to global ischaemia (35 min) and reperfusion (60 min), for 30 min before ischaemia or during the first 15 min of reflow. Infarct size was significantly reduced when postRIC dialysate was applied before ischaemia as compared with hearts pretreated with control dialysate (44.81 ± 3.22 vs. 55.55 ± 2.53%, P  = 0.012, n  = 12). Blockade of glycine receptors with strychnine 10 μM inhibited the protective effect caused by pretreatment with postRIC dialysate (52.76 ± 6.94 vs. 51.92 ± 5.78%, P -NS, n  = 5), whereas pretreatment with glycine 3 mmol/L, but not succinate 100 μmol/L, mimicked RIC protection (41.90 ± 4.50% in glycine-treated vs. 61.51 ± 5.16 and 64.73 ± 4.47% in succinate-treated and control hearts, respectively, P  < 0.05, n  = 4–7). Conclusions: RIC releases glycine and exerts cross-species cardioprotection against infarction through glycine receptor activation.